2019
DOI: 10.1111/cup.13605
|View full text |Cite
|
Sign up to set email alerts
|

Neurofibromas of the oral and maxillofacial complex: A 48‐year retrospective study

Abstract: Neurofibromas are benign neoplasms of the peripheral nerve sheath, characterized by the proliferation of Schwann cells, perineural cells and endoneural fibroblasts.Their occurrence in the oral and maxillofacial complex is uncommon. This study aimed to evaluate the clinical and histopathological characteristics of neurofibromas of the oral and maxillofacial complex excised at our institution over a 48-year period.Using light microscopy, two previously trained oral pathologists re-evaluated all hematoxylin and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…The oral clinical presentation includes gingival enlargement and pigmentation, dental abnormalities, dental caries, neoplastic lesions and osseous lesions. The tongue is the most commonly affected region of oral neuro broma [39]. In our study, the symptom of two cases were oral neoplastic lesion of NF-1 patients, both located in tongue, and only one patient's mother has similar clinical features.…”
Section: Neuro Bromamentioning
confidence: 49%
“…The oral clinical presentation includes gingival enlargement and pigmentation, dental abnormalities, dental caries, neoplastic lesions and osseous lesions. The tongue is the most commonly affected region of oral neuro broma [39]. In our study, the symptom of two cases were oral neoplastic lesion of NF-1 patients, both located in tongue, and only one patient's mother has similar clinical features.…”
Section: Neuro Bromamentioning
confidence: 49%
“…Conversely, Tamiolakis et al 39 reported granular cell tumor to be the most common neoplasm. Neural neoplasms can occasionally arise as intraosseous lesions 40,41 . As previously reported, neurofibroma was the most common neural tumor to arise in bone, with the posterior mandible the preferred site of occurrence 10,41‐43 .…”
Section: Discussionmentioning
confidence: 73%
“…The literature on benign CSTNs of the oral and maxillofacial region is somewhat scarce and most original articles are focused on a single tumor or a specific group of tumors 6‐55 . Therefore, the aim of the present study was to describe the demographic and clinical features of benign CSTNs occurring in the oral and maxillofacial region in order to (1) characterize benign oral and maxillofacial CSTNs as a group and (2) identify similarities and differences that could aid in the clinical differential diagnosis.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations